CAN COPPER AND ZINC IN DIFFERENT CHEMICAL FORMS CAN IMPROVE IRON DEFICIENT IN PHASEOLUS PLANT - & El Fouly, Salama (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was aimed to compare between the effects of different chemical forms of Zn and cupper[ionic forms (CuSO4), (Zn SO4) and chelated forms of [Cu Zn (II) HEDTA and Cu (II) HEDTA], whereas, HEDTA is N-(hydroxyethyl) ethylenediamine triacetic acid, applied at micromolar concentrations in the nutrient solution] of Phaseolus Vulgaris plants grown hydroponically under conditions of iron deficiency (- Fe) were investigated. Plant variants (– Fe + 2 µM Cu2+) and (– Fe+ 20 µM Zn2+) with extremely strong chlorosis were examined for investigations to take after the recuperation of leaf greening after treatment with Cu(II)HEDTA created leaf greening in the two variations, particularly strong for the recently which created leaf, as it appeared with chlorophyll estimations. Changes of plasma membrane reductase movement (PMRA) in roots after treatment with ionic or chelated copper were followed in (+Fe) and (– Fe) plants. The results show the increment of ferric-chelate reductase action (with substrate of Fe (III) HEDTA). Then, the cupric-chelate Cu (II) HEDTA, connected at similar level in arrangements with (– Fe) plants, kept up the high encouragement of plasma membrane ferric-chelate reductase activity. It can be concluded that the treatment with Cu (II) HEDTA enhanced the development and root plasma membrane reductase activity (PMRA) and additionally iron deficiency reactions of phaseolus plants. Regard to cell compounds increase, measurements of 20 μM of Zn altogether developed the action of the protein superoxide dismutase and peroxidase.